Transformation of school Cooperatives in Building a Student Entreprenurship Incubator Model Approach - Hendro Sugiarto; Nova Nurhanifah (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
This study aims to analyze and formulate a model for transforming school cooperatives into entrepreneurship incubators for students oriented toward sociopreneurship in Garut Regency. The research object includes junior and senior secondary schools that operate active school cooperatives. This study employed a qualitative descriptive approach, with data collected through in-depth interviews, participatory observation, and documentation studies involving school principals, cooperative managers, teachers, students, and external stakeholders. The data were analyzed using thematic analysis to identify patterns, challenges, and best practices in cooperative transformation. The findings indicate that most school cooperatives still operate conventionally and have not been optimally integrated into entrepreneurship learning. This study proposes a transformation model based on institutional strengthening, experiential learning integration, business incubation stages, and sociopreneurship orientation. The model positions school cooperatives as school-based business incubators that enhance students’ entrepreneurial competencies and social awareness.